An Analysis of Newspaper Reports on the Success of Individuals with Autism Spectrum Disorder - Gulsen Sencan; Yakup Burak (Journalism and Media)
This study aims to change the negative attitudes towards individuals with ASD, to analyse the news published about their success. The news reports published in The New York Times and The Washington Post newspapers, which were only about the success stories of individuals with ASD, were analysed by document analysis and content analysis, which are qualitative research methods. In this study, 40 news from the two international newspapers were analysed. It was revealed that success stories in the area of art were published more than other areas. In this study, it is noteworthy that the role of teachers, who are important sources of inspiration in the educational life of individuals with ASD, in success stories is quite low. In this respect, it may be suggested that in future studies, newspapers in the international newspapers may publish news in which the effect of teachers on the success stories of individuals with ASD is mentioned more.